Penerapan Pemasaran Digital pada UMKM D’kitchen untuk Meningkatkan Daya Saing di Era Digital - Dini Yani; Dexi Triadinda (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting the national economy but often face challenges in reaching broader markets in the digital era. This report focuses on the digital marketing strategies implemented by D'Kitchen, a culinary MSME that relies on social media and e-commerce platforms to enhance competitiveness. Actions taken include the implementation of various digital tools, such as Instagram, marketplaces, and e-payment systems, to measure their effectiveness in increasing visibility, market reach, and customer loyalty. The results of this report show that the application of digital marketing strategies successfully boosts consumer engagement and expands the market, although further optimization is still needed to sustain long-term growth. This report provides practical recommendations for MSMEs in leveraging digital technology to face increasingly competitive markets.